Back Analysis of the Initial Geo-Stress Field of Rock Masses in High Geo-Temperature and High Geo-Stress - Wei Meng; Chuan He (Energies, 2020)
In a high geo-temperature environment, it is rarely reported that geo-temperature has been considered during a back analysis. This may cause the initial geo-stress field that is obtained by a back analysis to be wrong. In this study, according to the theory of elasticity, the theoretical solution of the hydraulic fracturing equation is obtained in a high geo-temperature environment. Since the vertical stress that is obtained by the hydraulic fracturing method is calculated using the density of overlying strata, this vertical stress lacks the thermal stress that is caused by geothermal gradients. Therefore, in a high geo-temperature environment, inverting the initial geo-stress field of rock masses directly using the stress that is measured by the hydraulic fracturing method can cause serious errors. We propose that the regression coefficient of a gravitational stress field should be set to one during a back analysis if stresses are measured by the hydraulic fracturing method, and this regression coefficient should not be equal to one if stresses are measured by overcoring methods. We also propose a workflow for the back analysis of the initial geo-stress field of rock masses that considers geo-temperature, and this workflow is applied to the Sangzhuling tunnel in China.